Holistic Energy Education to Promote Energy Literacy—A Literature Review on Theoretical-Conceptual, Empirical, and Practical Teaching Approaches - Hermanussen, Carla; Raschke, Nicole; Wey, Lisa (Journal of Geography Education, 2024)
German-language geography didactics lacks systematic access to international, interdisciplinary discourses on energy education. In this article, the current state of research on energy education to promote energy literacy is presented, based on a comprehensive literature study. The focus is on theoretical-conceptual discussions, exploring different approaches to energy education, and summarizing key findings from empirical, practice-oriented studies. The aim is to offer an in-depth examination of energy education, refine its conceptual foundations, and establish the idea of holistic energy education. This serves to make the broad subject area compatible with a geography education perspective in the German-speaking world.
Keywords: energy education, renewable energies, energy literacy, education for sustainable development